A Facile Microwave Hydrothermal Method for Fabricating SnO2@C/Graphene Composite With Enhanced Lithium Ion Storage Properties - Liu, Li-Lai; Li, Ming-Yang; Sun, Yi-Han; Yang, Xue-Ying; Ma, Min-Xuan; Wang, Hui; An, Mao-Zhong (Frontiers in Chemistry, 2022)
SnO2@C/graphene ternary composite material has been prepared via a double-layer modified strategy of carbon layer and graphene sheets. The size, dispersity, and coating layer of SnO2@C are uniform. The SnO2@C/graphene has a typical porous structure. The discharge and charge capacities of the initial cycle for SnO2@C/graphene are 2,210 mAh g−1 and 1,285 mAh g−1, respectively, at a current density of 1,000 mA g−1. The Coulombic efficiency is 58.60%. The reversible specific capacity of the SnO2@C/graphene anode is 955 mAh g−1 after 300 cycles. The average reversible specific capacity still maintains 572 mAh g−1 even at the high current density of 5 A g−1. In addition, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) are performed to further investigate the prepared SnO2@C/graphene composite material by a microwave hydrothermal method. As a result, SnO2@C/graphene has demonstrated a better electrochemical performance.